Spherical silica and silica dispersion liquid containing the same
Patent Information
- Application Number
- CN202610527727.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-12-31
- Filing Date
- 2026-04-21
- Publication Date
- 2026-11-03
AI Technical Summary
Existing technologies make it difficult to achieve both dense and porous structures in spherical silica particles in cosmetic compositions at low cost and in mass production, resulting in insufficient oil absorption or poor durability.
By designing a gradient porous structure in spherical silica particles, the core part has larger pores and the shell part has smaller pores. The core and shell are continuously connected to form a dense and porous combination of particles. The pore size distribution is controlled to regulate the adsorption and release characteristics of the active ingredients.
It achieves a smooth feel, excellent adhesion and durability in cosmetic compositions, while maintaining stability in high-concentration dispersions, inhibiting precipitation and stratification, and providing a standard for quantitatively evaluating changes in the internal structure of dispersions.
Smart Images

Figure CN123026232A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to spherical silica and silica dispersions containing the same, and more specifically, to spherical silica and silica dispersions containing the same applicable to compositions in cosmetics, inks, coatings, adhesives, etc. Background Technology
[0002] Spherical microbeads used in cosmetic compositions are widely used to improve the feel of cosmetics, absorb sebum and sweat, and provide a soft, natural concealing effect.
[0003] The organic microbeads used in this study have advantages such as good adhesion, user experience and durability due to the unique physical properties of polymers, and are easy to mass-produce at low cost. However, since they are identified as the main cause of large amounts of microplastic emissions, environmentally friendly alternative materials are needed.
[0004] In response, silica (SiO2) has attracted attention as an environmentally friendly alternative material. Spherical silica particles possess excellent physical and chemical properties such as dielectric constant, moisture resistance, filling capacity, expansion rate, stress, and coefficient of friction, and are considered environmentally safe. Therefore, they have significant advantages for wide application in a wide range of industries, including electrical / electronic materials, pharmaceuticals, food, construction, and cosmetics.
[0005] The manufacturing methods for this spherical silica powder include dry methods (e.g., melt spraying, flame forming, gas phase metal combustion, aerosol process, etc.) and wet methods (e.g., sol-gel method, precipitation method, suspension method, emulsion method).
[0006] The wet process involves adding acids to water glass to precipitate silica at a pH of 2.0 to 5.0, removing impurities, followed by wet filtration and multiple drying steps. While the wet process offers the advantage of low-cost mass production, the resulting silica particles have a porous structure with relatively large pores, which reduces their usability in cosmetics and limits their application.
[0007] On the other hand, the dry process involves spraying a silica precursor as droplets or gas and then passing it through a reactor. Through nucleation and growth, particle growth, and sintering, a chemical reaction is induced, and spherical silica particles are produced through particle separation and recycling. The dry process has the advantage of producing particles with high sphericity and high purity. However, due to high initial installation costs, silica particles manufactured using the dry process are expensive. Furthermore, these silica particles have only micropores smaller than 1 to 2 nm or have almost no pores, and have a high specific gravity, thus limiting their applicability.
[0008] Especially when used in cosmetic compositions, spherical silica produced by wet processing has difficulty controlling the release rate of active ingredients, resulting in poor durability when applied to cosmetic compositions; while silica produced by dry processing has low oil absorption capacity, resulting in poor oil absorption when applied to cosmetic compositions, leading to shine over time.
[0009] Therefore, there is a need for a method for growing and synthesizing spherical silica particles that can simultaneously achieve dense and porous structures within a single particle, while also enabling low-cost mass production.
[0010] Furthermore, the aforementioned background technology is technical information possessed by the inventors in order to arrive at the present invention, or technical information obtained in the process of arriving at the present invention, and cannot be considered as publicly known technology that was disclosed to the public before the application for the present invention.
[0011] Existing technical documents
[0012] Patent documents
[0013] (Patent Document 1) Japanese Patent No. 5230051, "Micro-Fused Silica Particles"
[0014] (Patent Document 2) Korean Patent No. 10-1441169, "Porous silica particles with smooth surface, method for manufacturing the same, and cosmetic product formulated with said porous silica particles"
[0015] (Patent Document 3) Korean Patent Publication No. 10-2008-0028992, "Hollow Silica Particles, Compositions Containing the Same, and Method for Manufacturing the Same" Summary of the Invention
[0016] Technical problems to be solved
[0017] One embodiment of the present invention aims to provide spherical silica and a dispersion containing the same, which can adjust the adsorption and release characteristics of active ingredients and improve oil absorption and persistence by controlling the pore size and distribution of silica particles.
[0018] One embodiment of the present invention aims to provide spherical silica and dispersions containing the thereof that can be mass-produced at low cost and are easily applied to cosmetic compositions.
[0019] Furthermore, one embodiment of the present invention aims to provide spherical silica as an environmentally friendly powder that can impart excellent adhesion and feel in cosmetic compositions, and a dispersion containing the same.
[0020] Furthermore, one embodiment of the present invention aims to provide spherical silica and a silica dispersion containing the same, which can suppress precipitation or stratification even when the spherical silica particles are dispersed at a high concentration in a dispersion medium, thereby maintaining long-term stability.
[0021] Furthermore, one embodiment of the present invention aims to provide a spherical silica and a silica dispersion containing the same, which provides a standard for quantitatively evaluating changes in the internal microstructure of the dispersion and the concentration gradient over time for the silica dispersion.
[0022] Furthermore, one embodiment of the present invention aims to provide a spherical silica and a silica dispersion containing the same, wherein the spherical silica particles simultaneously achieve a dense structure and a porous structure in a single particle, and its excellent dispersion stability is verified by quantitative indicators reflecting the relationship between internal pore structure, tap density and dispersion stability.
[0023] Technical solution
[0024] As a technical solution to solve the above-mentioned technical problems, according to one aspect of the present invention, spherical silica includes a plurality of spherical silica particles, each of the plurality of spherical silica particles including: a core containing a plurality of first pores and made of silica; and a shell made of the same silica as the core and containing second pores different from the first pores.
[0025] According to another aspect of the invention, the core and the shell can be continuously connected along the central direction in the spherical silica particles to form a body.
[0026] According to another aspect of the invention, the first pore may have a size of less than 100 nm, and the second pore may have a size of less than 20 nm.
[0027] According to another aspect of the invention, the size of the second pore may gradually increase from the shell to the core, and at the position where the shell and the core are in contact, the size of the second pore may be the same as the size of the first pore.
[0028] According to another aspect of the invention, the tap density of the spherical silica particles, as measured by any of the methods in ASTM B527, ISO 787 and JISK 5101, can be from 0.40 g / mL to 0.95 g / mL.
[0029] According to another aspect of the invention, the average particle size (D50) measured by particle size analysis (PSA) can be from 0.5 to 30 μm.
[0030] According to another aspect of the invention, the thickness of the core may be less than 99% of the total diameter of the cross-section of the spherical silica particles.
[0031] According to another aspect of the invention, the thickness of the shell may be less than 50% of the total diameter of the cross-section of the spherical silica particles.
[0032] According to another aspect of the invention, the oil absorption of the powder obtained from oil absorption analysis (OA) can be from 0.2 to 120 mL / g.
[0033] According to another aspect of the invention, the specific surface area obtained from specific surface area analysis (BET) can be 100 m². 2 / g or less.
[0034] According to another aspect of the invention, the spherical silica particles are configured to adsorb and desorb substances through the plurality of first pores and second pores, wherein the relative pressure applied to the spherical silica particles for adsorption and the relative pressure applied to the spherical silica particles for desorption may be different.
[0035] As a technical solution to solve the above-mentioned technical problems, according to another aspect of the present invention, the silica dispersion is characterized in that it includes a dispersion medium and spherical silica dispersed in the dispersion medium, wherein the spherical silica includes a core containing a plurality of first pores and composed of silica, and a shell composed of silica of the same type as the core and containing second pores different from the first pores.
[0036] According to another aspect of the invention, the spherical silica may be contained in the dispersion medium at a concentration of 10 wt% to 20 wt%, based on the solid content.
[0037] According to another aspect of the invention, the Turbiscan Stability Index (TSI) of the silica dispersion, measured using a Turbiscan apparatus at 25°C, can be less than 0.30.
[0038] According to another aspect of the invention, the dispersion medium may include at least one of hydrocarbon oils, ester oils, vegetable oils, and silicone oils.
[0039] Technical effect
[0040] According to any one of the solutions to the problem described above, the spherical silica of the present invention has a gradient porous feature, that is, the pore size gradually decreases from the core center to the outer shell periphery. Due to this structural feature, it can be distributed into uniform particles with high sphericity, thereby providing a soft and silky application feel to the skin, uniformly adhering to the skin surface, and offering the advantages of excellent adhesion and durability when applied to cosmetic compositions.
[0041] Furthermore, according to any one of the solutions to the problem according to the present invention, spherical silica comprises a core with relatively large pores and a shell with relatively small pores, and has the characteristic of being able to precisely control the thickness of the core and shell. This feature, when applied to cosmetic compositions, can effectively regulate the oil and moisture balance on the skin, thus having the advantage of being customizable according to product application or skin type.
[0042] Furthermore, according to any one of the solutions to the problem according to the present invention, spherical silica is a material with very high chemical stability and high biocompatibility. Since it does not contain synthetic polymers, organic matter, or harmful components, it has the advantage of being usable as an environmentally friendly material.
[0043] Furthermore, according to any one of the solutions to the problem according to the present invention, the spherical silica of the present invention has a gradient porous characteristic, that is, the pore size gradually decreases from the core center to the outer shell periphery, and has a tap density controlled between 0.40 g / mL and 0.95 g / mL according to standard specifications. Through the above-described structural features, the spherical silica has the advantage of being able to maintain a more stable floating state in a dispersion medium.
[0044] Furthermore, according to any one of the solutions to the problem according to the present invention, the silica dispersion of the present invention has the following characteristics: spherical silica with a gradient porous structure is contained in the dispersion medium at a concentration of 10 wt% to 20 wt%, based on the solid content. Due to the above-mentioned structural characteristics, the spherical silica contained in the silica dispersion at a high concentration can more uniformly exert its original functions such as improving tactile feel, imparting optical properties, and adjusting viscosity within the silica dispersion, without agglomeration or precipitation.
[0045] Furthermore, according to any one of the solutions to the problem according to the present invention, the silica dispersion of the present invention has the following technical feature: the TSI measured using a Turbiscan device at 25°C is controlled below 0.30. Through this structural feature, not only can sedimentation driving forces be effectively suppressed in silica dispersions with high solids concentrations, but even if the spherical silica particles agglomerate during product use, they are relatively easy to redisperse, thus exhibiting less viscosity and appearance change during long-term storage or use.
[0046] Furthermore, according to any one of the solutions to the problem presented in this invention, the technical feature is that the tap density of the spherical silica and the TSI value of the silica dispersion both meet specific values, resulting in small or almost no deviations in backscattering intensity and transmittance on the BS / T spectrum. Due to the aforementioned structural features, the excellent dispersion stability of silica dispersions containing high concentrations of gradient porous spherical silica can be quantitatively defined, thereby offering the advantage of effectively managing batch-to-batch fluctuations in production and quality management.
[0047] The effects that can be obtained by the present invention are not limited to those mentioned above. Those skilled in the art to which this invention pertains will clearly understand other effects not mentioned below through the description below. Attached Figure Description
[0048] Figure 1 This is a scanning electron microscope (FE-SEM) image of the cross-section of a spherical silica particle according to an embodiment of the present invention.
[0049] Figure 2 This is a flowchart of a method for manufacturing spherical silica according to an embodiment of the present invention.
[0050] Figure 3 This is a scanning electron microscope (FE-SEM) image of the cross-section of the spherical silica particles prepared according to Example 1 of the present invention.
[0051] Figure 4 This is a scanning electron microscope (FE-SEM) image of the cross-section of the spherical silica particles prepared according to Example 2 of the present invention.
[0052] Figure 5 The image shown is a scanning electron microscope (FE-SEM) image of the cross-section of silica particles according to Comparative Example 2 of the present invention.
[0053] Figure 6 This is a transmission electron microscope (TEM) image of the cross-section of the spherical silica particles prepared according to Example 1 of the present invention.
[0054] Figure 7 This is a transmission electron microscope (TEM) image of the cross-section of a spherical silica particle according to Comparative Example 1 of the present invention.
[0055] Figure 8 This is a scanning electron microscope (FE-SEM) image of the surface of the spherical silica particles prepared according to Example 1 of the present invention.
[0056] Figure 9a and Figure 9b The nitrogen adsorption-desorption isotherms of the spherical silica particles prepared according to Examples 1 and 2 of the present invention are shown.
[0057] Figures 9c to 9e The nitrogen adsorption-desorption isotherms of silica particles according to Comparative Examples 1 to 3 of the present invention are shown.
[0058] Figure 10 It is a graph showing the change in Turbiscan Stability Index (TSI) of a silica dispersion containing spherical silica prepared according to Example 1 of the present invention.
[0059] Figure 11 It is a graph showing the change in Turbiscan Stability Index (TSI) of a silica dispersion containing spherical silica prepared according to Example 2 of the present invention.
[0060] Figure 12 It is a graph showing the change in Turbiscan Stability Index (TSI) of a silica dispersion containing spherical silica according to Comparative Example 1 of the present invention.
[0061] Figure 13 It is a graph showing the change in Turbiscan Stability Index (TSI) of a silica dispersion containing spherical silica according to Comparative Example 2 of the present invention.
[0062] Figure 14 It is a graph showing the changes in transmittance and backscattering intensity of a silica dispersion containing spherical silica prepared according to Example 1 of the present invention.
[0063] Figure 15 It is a graph showing the changes in transmittance and backscattering intensity of a silica dispersion containing spherical silica prepared according to Example 2 of the present invention.
[0064] Figure 16 It is a graph showing the changes in transmittance and backscattering intensity of a silica dispersion using spherical silica according to Comparative Example 1 of the present invention.
[0065] Figure 17It is a graph showing the changes in transmittance and backscattering intensity of a silica dispersion using spherical silica according to Comparative Example 2 of the present invention.
[0066] Explanation of reference numerals in the attached figures
[0067] 100: Spherical silica particles
[0068] 110: Nuclear
[0069] 111: First pore
[0070] 120: Shell
[0071] 121: Second pore Detailed Implementation
[0072] The embodiments of the present invention will now be described in detail with reference to the accompanying drawings to enable those skilled in the art to readily implement the invention. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. Furthermore, in the drawings, parts unrelated to the description have been omitted for clarity, and similar reference numerals have been used for similar parts throughout the specification.
[0073] Throughout the specification, when describing a connection between one part and another, it includes not only direct connections but also indirect connections involving other components or elements. Furthermore, when describing a part as "containing" a constituent element, unless specifically stated otherwise, it does not exclude other constituent elements but rather implies that other constituent elements may be included.
[0074] The present invention will now be described in detail with reference to the accompanying drawings.
[0075] The spherical silica of the present invention is a powder material comprising silica particles having a microparticle size of hundreds of nanometers (nm) to tens of micrometers (μm). In particular, the silica particles constituting the spherical silica of the present invention are spherical particles containing multiple pores, through which specific liquids can be adsorbed or gradually released after containing active ingredients to provide a variety of functionalities.
[0076] The spherical silica of the present invention has the characteristic that the cross-sectional pore structure of each spherical silica particle constituting it varies with region. The cross-sectional characteristics of each spherical silica particle constituting the spherical silica of the present invention will be described below.
[0077] Figure 1This is a scanning electron microscope (FE-SEM) image of a spherical silica cross section according to an embodiment of the present invention.
[0078] Reference Figure 1 The spherical silica particles 100 of the present invention include a core 110 and a shell 120 surrounding it.
[0079] The core 110 of the spherical silica particle 100 refers to the portion corresponding to the central region of the spherical silica particle 100.
[0080] The core 110 of the spherical silica particle 100 includes a first pore 111. The core 110 can be defined as a region in the internal region of the spherical silica particle 100 in which the first pore 111 is distributed.
[0081] In the spherical silica particles 100, the core 110 can be a sphere extending from the center along a predetermined diameter in the xyz direction. However, it is not limited to this, and the shape of the core 110 can be configured in various ways. As mentioned above, the core 110 is defined as the region in the internal region of the spherical silica particles 100 in which the first pores 111 are distributed. Therefore, the shape of the core 110 can be constructed into various forms such as circular, elliptical, and polygonal structures according to the distribution of the first pores 111.
[0082] The first pore 111 is a pore located in the core 110, which refers to a physically hollow space that does not contain elements that constitute silicon dioxide.
[0083] In the core 110, the first pore 111 can be constructed as a sphere. However, it is not limited to this, and the shape of the first pore 111 can be constructed in a variety of ways. As mentioned above, the first pore 111 is defined as a physically hollow space in the core 110 that does not contain elements constituting silicon dioxide. Therefore, the shape of the first pore 111 can be constructed into various shapes such as elliptical or polygonal structures, depending on the arrangement of the elements constituting silicon dioxide.
[0084] The first pore 111 is composed of relatively large pores present within the spherical silica particles 100. For example, the first pore 111 preferably has a size of 150 nm or less. More preferably, the first pore 111 may have a size of 100 nm or less.
[0085] The size of the first pore 111 can gradually change from the periphery of the core 110 towards the center. For example, as the diameter of the core 110 increases, the first pore 111 can increase proportionally. That is, the first pore 111 can gradually increase in size along the radial direction. The first pore 111 has a gradient porous structure in which the size increases closer to the center of the core 110 and decreases further away from the center.
[0086] The first pores 111 can be uniformly distributed throughout the entire region of the core 110. As described above, since the size of the first pores 111 gradually decreases towards the periphery, it may appear that the pores are more distributed in the center overall.
[0087] The thickness of the core 110 formed by the distribution of the first pores 111 can be less than 99% of the total diameter of the cross section of the spherical silica particles 100.
[0088] When the thickness of the core 110 exceeds 99%, most of the area of the particle is composed of the core 110, and the boundary between the shell 120 and the core 110 is indistinguishable, which can be substantially the same as the spherical silica particle 100 with large pores.
[0089] Shell 120 refers to the outer region surrounding the spherical silica particles 100 of the core 110. Shell 120 is made of the same silica as the core 110 and contains second pores 121 that are different from the first pores 111. Specifically, shell 120 refers to the region within the spherical silica particles 100 where the second pores 121 are distributed.
[0090] The shell 120 can be configured to enclose the core 110. For example, it is preferable to form a spherical periphery that encloses the spherical core 110.
[0091] The second pore 121 is a hole provided in the shell 120, which refers to a physically hollow space that does not contain elements that constitute silicon dioxide.
[0092] The second pore may have a shape substantially similar to the first pore 111 of the core 110. That is, the second pore 121 may be constructed as a sphere, but is not limited thereto. The shape of the second pore 121 may be constructed as an ellipse, a polygonal structure, or other shapes other than a sphere.
[0093] The second pore 121 is composed of relatively small pores present within the pores of the spherical silica particles 100. For example, the second pore 121 preferably has a size of 60 nm or less. More preferably, the second pore 121 may have a size of 50 nm or less.
[0094] The thickness of the shell 120 with the second pores 121 can be configured to be less than 50% of the total diameter of the cross-section of the spherical silica particles 100.
[0095] When the thickness of the shell 120 exceeds 50%, the connectivity between the pores decreases and the capillary force weakens as the area with relatively small pore size second pores 121 expands. Furthermore, as the distance that the material absorbed inside the core 110 diffuses out through the shell 120 increases, the rate at which the material inside the core 110 is released to the outside may significantly slow down.
[0096] According to one embodiment of the present invention, the core 110 and the shell 120 are continuously connected along the central direction in spherical silica particles 100 to form a body.
[0097] In other words, the core 110 and shell 120 refer to the regions divided within the spherical silica particles 100, which are single particles. Here, a single particle refers to a particle composed of a single component, which is a concept that is different from secondary particles formed by the aggregation of multiple particles, or particles formed by the aggregation of multiple particles and the coating around the aggregate.
[0098] Since the spherical silica particles 100 of the present invention are composed of single particles, the pore characteristics such as pore size, pore volume, and specific surface area can be uniformly maintained throughout the particle, and stress concentration hardly occurs at the interface between the core 110 and the shell 120, thus improving the durability of the particles.
[0099] As described above, according to one embodiment of the present invention, the first pore 111 of the core 110 and the second pore 121 of the shell 120 may have different sizes. In this case, the size of the second pore 121 gradually increases from the shell 120 to the core 110 of the spherical silica particles 100, and at the position where the shell 120 and the core 110 meet, the size of the second pore 121 may be the same as the size of the first pore 111. That is, in the spherical silica particles 100, the pore size can be distributed in a form that gradually decreases from the center of the core 110 towards the surface of the shell 120. Accordingly, in terms of pore size and distribution characteristics, a gradient porous structure is formed in which relatively large pores are distributed in the core 110 and relatively small pores are distributed in the shell 120.
[0100] According to one aspect of the invention, the shape of the spherical silica particles 100 may be a sphere with high sphericity, but is not limited thereto. For example, the spherical silica particles 100 may have an elliptical shape or a partially concave shape of a sphere.
[0101] The spherical silica of the present invention can be composed of spherical silica particles 100 having the above-described characteristics. In this case, according to particle size analysis (PSA), the average particle size (D50) of the spherical silica particles 100 can be 0.5 to 30 μm.
[0102] When the average particle size of spherical silica particles 100 is less than 0.5 μm, the surface energy of the particles becomes high, resulting in severe aggregation, making it difficult to separate them into monodisperse particles with a single particle size.
[0103] When the average particle size of spherical silica particles 100 exceeds 30μm, when applied to cosmetic compositions, the large particles agglomerate and cannot be spread evenly, thus reducing spreadability. Upon contact with the skin, the large particles may feel rough or cause irritation to sensitive skin, resulting in a decreased user experience. Furthermore, the adhesion of large particles may decrease due to their low ability to fill skin depressions.
[0104] In the spherical silica particles 100 of the present invention, the specific surface area, as measured by specific surface area analysis (BET), is 100 m². 2 / g or less.
[0105] When the specific surface area of spherical silica particles exceeds 100m² 2 At a concentration of / g, the number of surface active sites (e.g., silanol groups) increases, which can improve the adsorption capacity. Therefore, in addition to the target substance, unwanted molecules (e.g., organic matter, ions, etc.) are adsorbed, which can cause side reactions.
[0106] In the spherical silica particles 100 according to one embodiment of the present invention, the oil absorption of the powder, as measured by oil absorption analysis (OA), can be less than 130 mL / g. Preferably, it can be from 0.2 to 120 mL / g.
[0107] When the oil absorption of the powder exceeds 120 mL / g, the powder particles may clump together or become like a paste and lose their fluidity due to excessive liquid absorption through the pores within the spherical silica particles 100.
[0108] When the oil absorption capacity of the powder is less than 0.2 mL / g, not only can the oil molecules not effectively penetrate into the spherical silica particles 100, but the interaction with the oil molecules is also weak, which can lead to a decrease in adsorption force.
[0109] As described above, the spherical silica particles 100 according to an embodiment of the present invention have a dual structure: a core 110 with relatively large first pores 111 and a shell 120 enclosing it with relatively small second pores 121. This structure improves the sphericity of the particles, enabling a smooth and well-defined overall shape, which helps to provide a soft and silky feel to the skin when applied to cosmetic compositions. Furthermore, the spherical silica of the present invention is a stable material, free of biodegradable organic matter or harmful components, and exhibits minimal skin irritation, making it an environmentally friendly material with a low environmental impact.
[0110] The spherical silica particle 100 of the present invention includes a core 110 comprising a plurality of first pores 111 and made of silica, and a shell 120 enclosing the core 110 and comprising second pores 121 of different sizes than the first pores 111. The core 110 and the shell 120 are made of the same silica material and are formed into a single particle by forming a structure that is continuously connected in the central direction. This ensures the structural stability of the entire particle and allows it to have a uniform shape.
[0111] In particular, the core 110 at the center has first pores 111 with an average diameter of less than 100 nm, while the outer shell 120 has second pores 121 with an average diameter of less than 50 nm. This dual structure that divides pore size allows for fine differentiation of porosity characteristics within a single particle, contributing to improved functionality. Furthermore, because the pore size in each region of the core 110 and shell 120 is strictly controlled, the particle has high sphericity, and the overall pore size and density can be maintained uniformly. As a result, silica particles with smooth surfaces and well-defined morphologies can be achieved.
[0112] This structure allows for the phased adsorption and release of active ingredients, which is effective in improving the delivery efficiency and durability of functional ingredients when applied to cosmetic compositions. In particular, the micropores formed on the shell 120 can effectively absorb impurities such as sebum or oil, helping to improve the durability of makeup and control shine.
[0113] Furthermore, the spherical silica particles 100 of the present invention, possessing high sphericity and a uniform and gradient pore distribution, provide a smooth and silky application feel when applied to the skin. Interparticle friction is minimized, resulting in virtually no rough texture felt on the skin, and the particles are evenly distributed on the skin surface to enhance usability. In addition, due to their high sphericity, the particles adhere well to the skin, thus exhibiting excellent adhesion and durability in cosmetic compositions.
[0114] On the other hand, the spherical silica particles 100 of the present invention have a structure in which the pore size gradually increases from the shell 120 towards the core 110. Due to this structure, at the junction of the shell 120 and the core 110, the sizes of the first pore 111 and the second pore 121 naturally connect, achieving continuity and a gradual change in pore size. This structure allows the active ingredient to diffuse or be released gently from the shell 120 towards the core 110, thereby effectively constructing a material movement path throughout the particle. As a result, delivery efficiency and durability are further improved, resistance to material movement is reduced, and a gentler user experience is provided while minimizing skin irritation.
[0115] On the other hand, according to an embodiment of the present invention, the spherical silica particles 100 are configured to adsorb and desorb substances through a plurality of first pores and second pores, and are configured such that the relative pressure to be applied to the spherical silica particles 100 for adsorption is different from the relative pressure to be applied to the spherical silica particles 100 for desorption.
[0116] That is, the spherical silica particles 100 of the present invention have a dual structure consisting of a core 110 and a shell 120, and this structural characteristic has a significant impact on the adsorption and desorption behavior of gases (or liquids). Assuming that a certain pressure is applied to induce adsorption or desorption in the spherical silica particles 100, under the same relative pressure, the adsorption volume and desorption volume of the gas (or liquid) are different from each other. For example, under the same relative pressure, the adsorption volume of the gas (or liquid) is smaller than the desorption volume.
[0117] This is believed to be due to the structure in which the relatively wide pores inside the spherical silica particles are connected by a relatively narrow neck. Firstly, during adsorption, as the relative pressure increases, gas first undergoes capillary condensation inside the pores rather than at the neck, thus filling the pores before filling the neck. Conversely, during desorption, the spherical silica 100 exhibits an ink-bottle effect due to the size difference between the pores and the neck, requiring relatively higher pressures for desorption.
[0118] The neck refers to the narrow channel connecting the pores, which is also the path through which matter can move inside the spherical silica particles 100. It is a concept distinct from the pores themselves.
[0119] On the other hand, the spherical silica particles 100 of the present invention are characterized by a gradient structure and a gradation structure in which the pore size gradually decreases from the core 110 to the shell 120. This gradient pore structure can further enhance the adsorption-desorption behavior generated by the aforementioned relative pressure change. That is, the structure in which the pore size gradually decreases from the core 110 to the shell 120 can gradually enhance the ink bottle effect and expand the asymmetry of the adsorption-desorption path. As a result, the desorption pressure increases, and gases (or liquids) can be adsorbed for a longer period of time.
[0120] Specifically, the closer to the center of the core 110, the larger the size of the first pore 111. As a result, the smaller the neck size connecting the first pore 111 with the adjacent peripheral pores 111 and 121 is compared to the pores 111 and 121, the greater the size difference, and thus the greater the mass transfer effect.
[0121] As a result, in the spherical silica particles 100 of the present invention, a pressure hysteresis occurs between the adsorption and desorption of gas (or liquid), meaning that the adsorption and desorption pathways are different. This hysteresis is particularly pronounced due to the size differences between the pores and necks, the interconnection structure of the pores, and the spatial arrangement of the pores. Through these factors, the spherical silica particles 100 are not sensitive to changes in external environmental pressure and can stably retain matter inside.
[0122] Furthermore, due to the structure of the spherical silica particles 100, the relative pressure required for desorption is greater than that required for adsorption, so that the gas (or liquid) adsorbed in the pores of the spherical silica particles 100 is only released when the environment changes (e.g., temperature / pressure drop, etc.), thereby providing a slow-release effect.
[0123] On the other hand, according to an embodiment of the present invention, the tap density of spherical silica powder, measured by any of the methods in ASTM B527, ISO 787 and JIS K 5101, can be from 0.40 g / mL to 0.95 g / mL.
[0124] When the tap density of spherical silica falls within the range described above, the spherical silica particles exhibit a gradient porous structure, increasing the internal pore volume and thus reducing the weight per unit volume. As a result, when spherical silica is dispersed in the dispersion medium described later, interparticle aggregation is suppressed or reduced, making it easier to disperse in the dispersion medium.
[0125] In addition to the methods mentioned above, any standard test method widely used in this technical field can be used without restriction to measure tap density.
[0126] Figure 2 This is a flowchart illustrating a method for manufacturing spherical silicon dioxide according to an embodiment of the present invention.
[0127] Reference Figure 2 In order to manufacture the spherical silica of the present invention, an emulsion forming step S210 is first performed to manufacture an emulsion containing a silica precursor.
[0128] The emulsion forming step S210 may include a first solution forming step, a second solution forming step, and a mixing step. Each step will be described in detail.
[0129] First, a first solution forming step is performed, in which a nonionic surfactant is dissolved in oil to form a first solution.
[0130] The first solution formation step is the step of forming a water-in-oil (W / O) emulsion in which oil is the continuous phase and water is the dispersed phase.
[0131] In the first solution formation step, the oil, as a nonpolar solvent, may include one or more compounds selected from kerosene, paraffin oil, diesel, xylene, toluene, hexane, heptane, octane, nonane, decane, undecane, and dodecane.
[0132] In the first solution formation step, the nonionic surfactant may include one or more compounds selected from propylene glycol monostearate, sorbitan sesquioleate, glycerol monostearate, sorbitan monoooleate, and sorbitan monostearate.
[0133] In the first solution formation step of the method for manufacturing spherical silica according to an embodiment of the present invention, a nonionic surfactant may be added at a content of 0.5 to 5 wt% relative to the total weight of the first solution.
[0134] If the nonionic surfactant content is less than 0.5 wt% in the first solution formation step, the interfacial tension between oil and water (or polar solvent) cannot be sufficiently reduced, which may prevent proper emulsification in the subsequent emulsion formation step S210. Consequently, droplets within the emulsion cannot be stably dispersed in the oil phase, and phase separation may easily occur over time. Furthermore, the droplet size within the emulsion increases, leading to aggregation and potentially making the emulsion unstable. Because the droplets cannot remain stable in the emulsion formation step S210, the silica precursor cannot gel uniformly in the subsequent gelation steps S230 and S240, potentially resulting in inconsistent pore structures.
[0135] In the first solution formation step of the method for manufacturing spherical silica according to an embodiment of the present invention, the nonionic surfactant may have a hydrophilic-lipophilic balance (HLB) value of 3 to 6.
[0136] In the first solution formation step, when the nonionic surfactant has an HLB value of less than 3, although the nonionic surfactant is easily soluble in the oil phase, its interaction with water becomes weaker and it cannot effectively act on the interface between oil and water. As a result, the size of the oil droplets increases, and the emulsion becomes unstable in the emulsion formation step S210, which may lead to stratification.
[0137] Conversely, when the nonionic surfactant in the first solution formation step has an HLB value exceeding 6, it exhibits strong hydrophilicity and is therefore more readily soluble in the aqueous phase, resulting in weaker interaction with the oil phase and potentially making emulsification difficult. This can lead to uneven droplet distribution during emulsion production in the emulsion formation step S210. Furthermore, ionic interactions with gelling agents such as sulfuric acid added in the gelation step may hinder the formation of the silica network.
[0138] After the first solution formation step, a second solution formation step is performed, in which the silica precursor is dissolved in distilled water to form a second solution.
[0139] In the second solution formation step, the silica precursor, as an aqueous solution containing a silica inorganic compound, may include one or more compounds selected from sodium silicate, lithium silicate, potassium silicate, and calcium silicate.
[0140] Preferably, in the second solution formation step of the present invention, the silica precursor may be composed of sodium silicate. In this case, the silica precursor may contain sodium oxide and silica in a molar ratio ranging from 1:2 to 1:3.4, and the silica content may be 5 to 30 wt% of the total weight of sodium silicate.
[0141] In the second solution formation step, when silica is included in sodium silicate at a content of less than 5 wt%, the interfacial activity of sodium silicate decreases, and the ability to maintain the stability of droplets in the emulsion in the emulsion formation step S210 may be reduced.
[0142] Specifically, the interfacial activity of sodium silicate is determined by the composition ratio of silica (SiO2) to sodium oxide (Na2O). Therefore, if silica is insufficient, its hydrophilic properties weaken, potentially reducing the stability of droplets within the emulsion. The colloidal properties of the sodium silicate aqueous solution also weaken, making droplet coalescence more likely. Consequently, silica network formation becomes difficult, and structural defects may occur during subsequent gelation steps.
[0143] On the other hand, when silica is included in sodium silicate at a concentration exceeding 30 wt% in the second solution formation step, the viscosity of the sodium silicate aqueous solution increases sharply, potentially making the emulsification process difficult. The increased concentration of the silica precursor leads to a faster gelation reaction, resulting in an uneven gel structure and making it difficult to form a uniform porous structure. Furthermore, the increased particle size or agglomeration within the emulsion can cause turbidity, which may affect the appearance quality of the final product.
[0144] After the second solution formation step, a mixing step is performed to combine the first solution produced in the first solution formation step and the second solution produced in the second solution formation step.
[0145] In the mixing step, the first solution and the second solution are vigorously stirred for 10 to 20 minutes by a homogenizer at a constant rotation speed of 200 to 1000 rpm.
[0146] As described above, vigorous stirring at a constant rotational speed of 200 to 1000 rpm for 10 to 20 minutes during the mixing step applies a high shear force to the oil-water interface, thereby miniaturizing the droplet size to the μm (or nm) level. Furthermore, it induces effective orientation of the nonionic surfactant and promotes uniform mixing of the oil and silica precursor, thus preventing phase separation and improving emulsion stability.
[0147] In the emulsion forming step S210 of the method for manufacturing spherical silica, the emulsion may be a mixture of oil and silica in a molar ratio ranging from 1:1 to 3:1.
[0148] When the molar ratio of oil and silica deviates from the aforementioned ratio, resulting in excessive oil mixing, the amount of nonionic surfactant becomes relatively insufficient, leading to larger droplet sizes and potential stratification. Furthermore, excess oil may dilute the silica precursor concentration, slowing down the gelation reaction or hindering gel formation. This can cause uneven pore size and distribution within the porous structure, potentially degrading the physical properties of the final product.
[0149] Through the above process, an emulsion is formed in the emulsion forming step S210.
[0150] After the emulsion formation step S210, a first gelation step S220 is performed to treat the emulsion to below room temperature.
[0151] The gelation step S220 is performed by maintaining the emulsion at a certain temperature. Maintaining the emulsion at a certain temperature can be performed while the emulsion is being introduced into a double-walled glass reactor. In this case, the aforementioned certain temperature is preferably below room temperature, more preferably 5 to 20°C.
[0152] Subsequently, a first gelling agent may be added in a gelling step S220.
[0153] The first gelling agent may include one or more compounds selected from ammonium bicarbonate (NH4HCO3), sodium bicarbonate (NaHCO3), potassium bicarbonate (KHCO3), ammonium carbonate ((NH4)2CO3), sodium carbonate (NaHCO3), ammonium sulfate ((NH4)2SO4), sodium sulfate (Na2SO4), ammonium nitrate (NH4NO3), sodium nitrate (NaNO3), ammonium chloride (NH4Cl), sodium chloride (NaCl), potassium chloride (KCl), ammonium phosphate ((NH4)3PO4), nitric acid (HNO3), hydrochloric acid (HCl), sulfuric acid (H2SO4), carbonic acid (H2CO3), boric acid (H3BO3), phosphoric acid (H3PO4), and carbon dioxide (CO2).
[0154] In a single gelation step S220, the first gelling agent can be added at a rate of 2 mL / min to 10 mL / min. By controlling the addition rate of the first gelling agent, the thickness of the shell 120 in the spherical silica particles 100 can be determined, and a dense structure of the shell 120 can be formed.
[0155] After the first gelation step S220, a second gelation step S230 is performed to treat the emulsion to above room temperature.
[0156] In the secondary gelation step S230, a second gelling agent may be added. The second gelling agent may be composed of the same material as the first gelling agent described above in the primary gelation step S220.
[0157] In the secondary gelation step S230, the second gelling agent may be sulfuric acid, more preferably a 30% sulfuric acid solution.
[0158] In the secondary gelation step S230, the aqueous solution obtained by the primary gelation step S220 is maintained at a certain temperature. This certain temperature is above room temperature, preferably 25°C or higher, and more preferably within the range of 30°C or higher.
[0159] These methods allow a shell to be formed within the silica particles.
[0160] During the secondary gelation step S230, the second gelling agent can be added at a rate of 2 mL / min to 5 mL / min.
[0161] On the other hand, in a method for manufacturing spherical silica according to an embodiment of the present invention, the secondary gelation step S230 may include adjusting the pH of the aqueous solution obtained by the primary gelation step S220 to 7.0 or higher. For example, the pH of the aqueous solution obtained by the primary gelation step S220 may be adjusted to 8.5. In this case, the step of adjusting the pH to 8.5 may be performed for 30 minutes to 1 hour. As described above, as the secondary gelation step S230 is carried out under alkaline conditions, the condensation reaction rate of the silica particles is regulated, thereby forming a uniform pore size. Furthermore, since the hydrolysis of the silica precursor is promoted, generating silanol (Si-OH) groups, the crosslinking density between silica particles increases, thus improving mechanical strength.
[0162] According to an embodiment of the present invention, a method for manufacturing spherical silica is characterized by forming spherical silica particles 100 through a primary gelation step S220 and a secondary gelation step S230. By controlling the gelation conditions of each gelation step, the size and density of the first pore 111 and the second pore 121 can be controlled, thereby controlling the thickness of the core 110 and the shell 120.
[0163] Specifically, in a single gelation step S220, the size and density of the second pores 121 of the shell 120 can be controlled by controlling the temperature and reaction rate at which the gelation reaction occurs. Specifically, the emulsion is introduced into a double-layered glass reactor and maintained at a temperature of 10°C. Subsequently, when the first gelling agent is introduced at a specific rate, the gelation reaction within the emulsion is gradually promoted, and surface reactions occur through the movement of droplets formed within the emulsion and the substances of the first gelling agent introduced into the emulsion. For example, a silica precursor diffuses to the droplet interface within the emulsion, forming a silica network through a condensation reaction at the interface, thereby forming a relatively dense shell with second pores 121 of less than 20 nm.
[0164] Subsequently, in the secondary gelation step S230, the hydrolysis and condensation reactions of the silica precursor are promoted by raising the temperature above room temperature and adjusting the pH, inducing the formation of a porous structure in the core 110, with the pore size potentially expanding to below 100 nm. On the other hand, the dense shell structure formed in the primary gelation step S220 exhibits high thermal stability, and structural deformation is limited even during the temperature increase in the secondary gelation step S230. Through this process, spherical silica particles 100 with different pore sizes in the core 110 and shell 120 are formed.
[0165] After the secondary gelation step S230, the spherical silica acquisition step S240 is performed to obtain spherical silica.
[0166] The step S240 for obtaining spherical silica involves heating, holding, solid-liquid separation, neutralization, and washing to obtain spherical silica.
[0167] The heating can be carried out at 80°C to 90°C, more preferably at 85°C.
[0168] When the temperature is raised to 85°C, the condensation reaction of the silanol groups remaining on the surface of the silica particles is promoted, which maximizes the density of siloxane bonds. Furthermore, due to the reduction in solution viscosity, this provides an effect that enables subsequent processing (such as centrifugation and filtration efficiency) to be carried out efficiently.
[0169] The residence time is for cooling the aqueous solution, and it is preferable to let the aqueous solution remain for more than 12 hours.
[0170] Subsequently, a solid-liquid separation step can be performed by physically separating the spherical silica particles 100 from the reaction liquid.
[0171] The above solid-liquid separation step is a step that separates the supernatant and performs centrifugal separation. It can be a step that removes unreacted precursors, residual surfactants, by-products, etc. from the spherical silica particles 100 to improve particle purity.
[0172] The subsequent neutralization and washing steps can be performed by washing with distilled water, ethanol, or a mixture thereof to adjust the pH and completely remove reaction byproducts.
[0173] Finally, a drying step can be performed to dry the spherical silica particles 100 that have undergone neutralization and water washing at a temperature of 80°C to 120°C for 20 to 50 hours.
[0174] Because the gelation steps S230 and S240 of the spherical silica manufacturing method according to an embodiment of the present invention are performed in two steps, silica single particles composed of a shell 120 with micropores and a core 110 with mesopores can be obtained. The spherical silica manufacturing method according to an embodiment of the present invention does not require the expensive initial equipment required by conventional dry processes, and overcomes the limitation that the entire particle has only a dense structure, making it difficult to use in cosmetic compositions. Furthermore, in conventional wet processes, the entire particle has a porous structure, but it is difficult to precisely control the pore size or distribution. The spherical silica manufacturing method of the present invention, through a two-step gelation process, can stepwise form a core 110 and a shell 120 with different pore sizes. This gelation step, by precisely adjusting the reaction conditions (temperature, pH, time, etc.), can adjust the ratio of core 110 / shell 120 or the size of pores 111 and 121, and is also suitable for manufacturing customized silica particles according to desired purposes. Therefore, by realizing a core 110 containing a first pore 111 smaller than 100 nm and a shell 120 containing a second pore 121 smaller than 50 nm within a single particle, the pore size distribution and spatial position can be precisely controlled. In particular, the spherical silica manufacturing method is based on a wet process, so the process conditions are easy to control, the scale of production equipment can be expanded, and it has the advantage of being very suitable for mass production in industry.
[0175] The spherical silica particles 100 of the present invention have a structural characteristic that allows for precise control of the thickness of the core 110 and shell 120, thus effectively regulating the oil-water balance of the skin when applied to cosmetic compositions. Specifically, the core 110, containing a first pore 111 of less than 100 nm, can absorb and store moisturizing ingredients (e.g., glycerin, hyaluronic acid, etc.) through its relatively large pores, thus providing a sustained moisturizing effect that supplies moisture to the skin for a long time. On the other hand, the shell 120, having a second pore 121 of less than 50 nm, can selectively adsorb low-molecular-weight substances such as sebum or oil components due to its smaller pore structure, which is effective in reducing skin shine. This dual-pore structure enables a selective regulation mechanism that maintains moisturizing ingredients while only adsorbing excess oil, ultimately helping to stabilize the skin's oil-water balance. Furthermore, since the thickness of the core 110 and shell 120 can be customized according to product application or skin type, it can be applied to various cosmetic series such as those for oily or combination skin.
[0176] Next, a silica dispersion containing spherical silica according to an embodiment of the present invention will be described in detail.
[0177] The silica dispersion of the present invention is a dispersion applicable to compositions such as cosmetics, inks, coatings and adhesives. It can suppress precipitation or stratification even when spherical silica particles are dispersed at a high concentration in a continuous phase, thereby enabling the creation of silica dispersions with a certain viscosity range depending on the application field.
[0178] Specifically, the silica dispersion of the present invention includes spherical silica and a dispersion medium.
[0179] The spherical silica of the present invention is a core component for ensuring excellent dispersion stability in dispersions with high solid concentrations. It is a powder material containing silica particles with microparticle sizes ranging from hundreds of nanometers (nm) to tens of micrometers (μm).
[0180] On the other hand, in this specification, "high concentration" can refer to a solids concentration above a level that typically leads to dispersion stability problems, such as 10 wt% or more, based on a silica dispersion. Furthermore, "medium concentration" can refer to a solids concentration of 3 wt% to 7 wt% based on a silica dispersion. Additionally, "low concentration" can refer to a solids concentration of less than 3 wt% based on a silica dispersion.
[0181] The spherical silica of the present invention can be used as a dispersed phase (or dispersed phase) that can be separately distributed in a continuous phase.
[0182] The spherical silica of the present invention is a single particle with a core-shell structure and gradient porous characteristics.
[0183] Because the spherical silicon dioxide of the present invention is similar to the previous reference Figure 1 The spherical silicon dioxide described is essentially the same, so a detailed description of it is omitted.
[0184] The dispersion medium of the present invention can be a medium that induces a uniform dispersion system, which does not induce the spherical silica as the dispersed phase to precipitate, stratify, or bridge and aggregate between particles within the medium, but rather allows each particle constituting the spherical silica to be separately distributed.
[0185] The dispersion medium of the present invention can be a continuous phase in which spherical silica can exist as the dispersion phase, preferably a medium in a liquid state.
[0186] First, the dispersion medium, as a continuous phase in a liquid state, can correspond to either an oil phase containing oil-soluble components or an aqueous phase containing water-soluble components; the types of liquid phase media are not limited to these.
[0187] Silica dispersions can also be achieved in the form of single dispersion or multiple dispersion systems.
[0188] On the other hand, when the dispersion medium is composed of an oil phase, the dispersion medium may include at least one of hydrocarbon oils, ester oils, vegetable oils, and silicone oils.
[0189] On the other hand, the silica dispersion of the present invention may be configured such that, based on the solids, spherical silica is contained in the dispersion medium at a concentration of 10 wt% to 20 wt%.
[0190] Preferably, the concentration can be 15 wt%, more preferably 20 wt%.
[0191] When the content of spherical silica in the dispersion medium exceeds 20 wt%, there is a risk of gelation or a sharp increase in viscosity due to the excessive concentration of spherical silica particles. That is, because the silica dispersion of the present invention contains spherical silica within the aforementioned suitable range in the dispersion medium, the multiple spherical silica particles in the dispersion medium do not aggregate, thereby achieving a silica dispersion with excellent dispersion stability.
[0192] Next, a method for manufacturing a silica dispersion according to an embodiment of the present invention will be described.
[0193] First, the step of mixing the spherical silica obtained according to the spherical silica manufacturing method of the present invention with a dispersion medium is performed.
[0194] Subsequently, in order to ensure that the spherical silica in the mixture is uniformly dispersed and does not agglomerate, a step is performed to convert the mixture into a silica dispersion using at least one of sonication, high-power stirring, and high-shear stirring techniques.
[0195] Finally, the step of creating a vacuum state in the obtained silica dispersion is performed to remove air bubbles.
[0196] The above-mentioned steps for removing air bubbles can be performed by transferring the silica dispersion to a vacuum oven and degassing it under vacuum, but are not limited to this method.
[0197] Next, the method for measuring the Turbiscan Stability Index (TSI) of silica dispersion according to an embodiment of the present invention will be described in detail.
[0198] TSI is a dimensionless index that is calculated by comprehensively reflecting the changes in backscattering intensity (BS) or transmittance (T) signals obtained by measuring with a Turbiscan device over time and in the height direction within a selected height range. It summarizes the overall development of physical instability phenomena such as sedimentation, creaming, flocculation, and coalescence that can be detected by changes in BS / T signals into a numerical representation.
[0199] TSI can quantitatively compare the changes in dispersion stability of multiple samples under the same measurement conditions and time reference, and can be used to determine the relative superiority or inferiority of the dispersion stability of each sample.
[0200] TSI can be measured using any of the common Turbiscan equipment such as Turbiscan LAB, Turbiscan Tower, Turbiscan AGS, and Turbiscan Classic, but is not limited to these.
[0201] To measure the TSI of a silica dispersion according to an embodiment of the present invention, the following method may be applied, for example.
[0202] The silica dispersion sample is filled to a predetermined height in the measurement cell, preferably to a height of about 55 mm or less.
[0203] Subsequently, the sample was irradiated with near-infrared (NIR) light using a Turbiscan device according to the set experimental conditions, and the corresponding BS and T signals were detected simultaneously.
[0204] The above experimental conditions can be varied according to the characteristics and composition of the sample to be tested. As one implementation method, the vertical resolution is about 40 μm, the time required for one scan is about 20 seconds, the scan cycle is about 30 minutes, and the total number of scans can be set to multiple times, such as tens to hundreds of times.
[0205] At this time, the preferred measurement temperature is about 25°C or higher, and the measurement time can be more than 2 hours.
[0206] In the BS / T spectrum obtained according to the above TSI measurement method, the x-axis is the same as the height (H) of the measurement cell, and the y-axis is the signal strength, which is BS (%) or T (%).
[0207] In this specification, "spectrum" refers to the distribution curve of the BS or T signal along the height of the measuring cell.
[0208] On the other hand, in the silica dispersion according to an embodiment of the present invention, the dispersed phase is contained in the dispersion medium at a concentration of 10 wt% to 20 wt% based on the solid content, which is a relatively high concentration sample. Therefore, the T spectrum measured according to the T signal can be close to 0 throughout the height range.
[0209] Therefore, the T spectrum measured based on the T signal can be close to 0 in most height ranges except for the meniscus.
[0210] Specifically, in the T spectrum of silica dispersion, for the region other than the meniscus, the scan spectrum measured multiple times can be less than 1% of the T baseline.
[0211] In this specification, "meniscus" refers to the curved area formed by surface tension in the upper boundary region of the sample in contact with air within the measurement cell, and is the region where light scattering signal distortion is prone to occur during Turbiscan measurement.
[0212] Therefore, in one embodiment of the present invention, the aforementioned meniscus region can be excluded from the height range to be analyzed when calculating TSI.
[0213] At this point, the aforementioned TSI can be calculated based on the following mathematical formula.
[0214]
Mathematical Formula 1
[0215]
[0216] Where, d i At each position h along the height of the measuring cell, the i-th scan spectrum Scani(h) and the (i-1)-th scan spectrum Scan i-1 The value is obtained by summing the absolute value of the signal difference between (h) over the height direction.
[0217] In addition, H represents the total height of the measuring cell (mm), i is the number of scans, and h refers to the positional variable in the height direction from the bottom to the top inside the measuring cell.
[0218] In addition, Scan i (h) is the signal value measured at the height h of the measuring cell at the i-th scan time point, which can be BS(%) or T(%).
[0219] That is, TSI can be defined as the value calculated by accumulating the signal difference between two consecutive scans measured at certain time intervals in the height direction based on the change in the dispersion stability of the sample. As the TSI value increases, it means that unstable phenomena such as sedimentation, floating, and agglomeration are taking place in the sample.
[0220] Regarding the silica dispersion of the present invention, the TSI measured using a Turbiscan device at 25°C may be, for example, 0.30 or less, preferably 0.25 or less.
[0221] When the TSI of the silica dispersion is within the range described above, the silica dispersion of the present invention can be evaluated as having excellent long-term dispersion stability.
[0222] In other words, even if the silica dispersion according to an embodiment of the present invention contains a high concentration of spherical silica, the sedimentation of spherical silica can be effectively suppressed even after long-term storage by maintaining the TSI value below 0.30. Furthermore, even if partial precipitation or stratification occurs, it exhibits the characteristic of being easily redispersible with a certain level of external force.
[0223] As described above, the silica dispersion according to one embodiment of the present invention is constructed such that, based on the solid content, spherical silica is contained in the dispersion medium at a concentration of 10 wt% to 20 wt%.
[0224] Due to the aforementioned structural characteristics, spherical silica contained in a high concentration of silica dispersion can more uniformly exert its original functions such as improving tactile feel, imparting optical properties, and adjusting viscosity within the silica dispersion, without agglomeration or precipitation.
[0225] For example, when the silica dispersion of the present invention is applied to a cosmetic composition, it not only provides a soft and silky application feel to the skin, but also improves adhesion and durability.
[0226] Furthermore, when the silica dispersion of the present invention is applied to an ink composition, the solid content is increased by dense filling, and the spherical silica is uniformly dispersed without agglomeration or precipitation, thereby improving the rheological properties and dispersion stability of the ink.
[0227] Furthermore, when the silica dispersion of the present invention is applied to adhesives, the filling rate is increased while the thermal stability and heat resistance are improved.
[0228] On the other hand, as described above, the silica dispersion according to one embodiment of the present invention comprises spherical silica, the spherical silica of the present invention comprising a core and a shell with different pore structures, and the tap density, measured by any one of ASTM B527, ISO 787 and JIS K 5101, is controlled to be between 0.40 g / mL and 0.95 g / mL.
[0229] Due to the aforementioned technical features, even under conditions of high solids concentration, the TSI value can be maintained at a low level below 0.30, resulting in spherical silica exhibiting a tendency to float stably in the dispersion medium.
[0230] In particular, as the tap density of the spherical silica is controlled within the range of 0.40 g / mL to 0.95 g / mL, the phenomenon of individual particles exhibiting different sedimentation behaviors due to gravity within the dispersion medium is reduced. Consequently, excessive sedimentation or buoyancy does not occur in the dispersion medium, and the particle behavior remains smooth, resulting in the induction of a stable dispersion state from the initial stage of forming the dispersion system in the dispersion medium.
[0231] Furthermore, because the silica dispersion of the present invention employs high-power stirring or high-shear stirring in the dispersion process, the relative positions and orientations of the spherical silica particles within the dispersion system can continuously change. Consequently, it is difficult for the particles to stably form mechanical interlocking, and the effect of further suppressing bridging and agglomeration within the dispersion system can be expected.
[0232] On the other hand, according to one embodiment of the present invention, the silica dispersion is configured such that the TSI measured using a Turbiscan device at 25°C is, for example, 0.30 or less.
[0233] Due to the aforementioned structural features, the silica dispersion of the present invention exhibits relatively little change in viscosity and appearance during long-term storage or use.
[0234] Specifically, when spherical silica is dispersed in a liquid medium, the excessive enhancement of interparticle interactions can be suppressed. Consequently, the formation of interparticle bridging and aggregation within the dispersion medium is reduced, resulting in excellent dispersion stability without stratification or sedimentation.
[0235] Furthermore, even if some agglomeration occurs during use, it tends to redisperse relatively easily, thus exhibiting relatively little change in viscosity and appearance during long-term storage or use.
[0236] Furthermore, since the tap density of the spherical silica and the TSI value of the silica dispersion are both limited to specific values according to an embodiment of the present invention, excellent dispersion stability can be quantitatively specified, thereby providing the advantage of effectively managing batch-to-batch fluctuations in production / quality management.
[0237] For example, the TSI index proposed in this invention can quantitatively explain the changes in dispersion stability over time, and therefore can be used to predict the possibility of future quality degradation such as deterioration. It can also be used as a reliability analysis index for design changes or redesigns, and is useful in quality management that changes over time.
[0238] The advantages of the spherical silica and silica dispersions containing the present invention will be described in more detail below through examples.
[0239] <Preparation Example - Preparation of Spherical Silica Particles>
[0240] First, spherical silica particles were prepared to compare and evaluate the porous characteristics of the spherical silica particles of the present invention.
[0241] Preparation Example 1. Preparation of spherical silica
[0242] The spherical silica according to Preparation Example 1 was prepared as follows.
[0243] Specifically, 241.29g of kerosene was used as the first solution.
[0244] 2.65 g of dehydrated sorbitan monooleate was used as the nonionic surfactant in the first solution.
[0245] The prepared raw materials were added and stirred to prepare the first solution.
[0246] Sodium silicate was used as the silica precursor for the second solution.
[0247] The second solution was prepared by stirring 250g of distilled water to achieve a silica concentration of 10wt% for sodium silicate.
[0248] The first and second solutions prepared above were mixed and stirred at 600 rpm for 20 minutes using a homogenizer to prepare an emulsion.
[0249] The first gelling agent was added dropwise to the above emulsion at a rate of 10 mL / min at a temperature of 10°C.
[0250] The first gelling agent mentioned above was prepared by adding 19.82g of ammonium sulfate to 300g of distilled water and stirring.
[0251] Subsequently, the reaction solution obtained in the first gelation step was maintained at a temperature of 35°C, and a second gelling agent was added dropwise at 5 mL / min to bring the pH of the reaction solution to 8.5.
[0252] The second gelling agent mentioned above used a 30% sulfuric acid solution.
[0253] The reaction solution obtained in the secondary gelation step is aged for 1 hour, and the gelation reaction is ended by heating to 85°C.
[0254] After cooling the reaction liquid for 12 hours and separating the kerosene from the supernatant, solid-liquid separation was carried out by centrifugation after neutralization. After two water washes, the slurry obtained by centrifugation was dried at 105°C for 48 hours to obtain the spherical silica powder of Preparation Example 1.
[0255] Preparation Example 2. Preparation of spherical silica
[0256] The spherical silica prepared in Preparation Example 2 used the same raw materials as in Preparation Example 1 and was prepared using the same preparation method.
[0257] Specifically, the first solution was prepared in the same manner as in Preparation Example 1, and the second solution was prepared by changing the silica concentration of sodium silicate to 15 wt%.
[0258] The emulsion formation step was carried out using the same method as in Preparation Example 1.
[0259] The first gelling agent was added dropwise to the emulsion at a rate of 2 mL / min under the same temperature conditions as in Preparation Example 1.
[0260] The first gelling agent mentioned above was prepared by adding 23.79g of ammonium sulfate to 300g of distilled water and stirring.
[0261] Subsequently, the reaction solution obtained in the first gelation step was maintained at a temperature of 10°C, and a second gelling agent was added dropwise at 2 mL / min to bring the reaction solution to pH 8.5.
[0262] The second gelling agent described above uses the same substance as in Preparation Example 1.
[0263] The same process as in Preparation Example 1 was performed starting from the secondary gelation reaction step.
[0264] The spherical silica powder of Preparation Example 2 was prepared by the above method.
[0265] Comparative Example 1. Porous spherical silica produced by wet process
[0266] Spherical silica powder with a porous structure, manufactured and commercially available through conventional wet processes, was used.
[0267] Comparative Example 2. Porous spherical silica produced by dry process
[0268] It uses spherical silica powder with a dense structure that is manufactured and commercially available through a conventional dry process (melt spraying).
[0269] Comparative Example 3. PMMA powder manufactured by organic powder method
[0270] Spherical PMMA (polymethyl methacrylate) powder with a dense structure, manufactured and commercially available via an organic powder method, was used.
[0271] <Experimental Example 1 - Comparison of Pore Structures Based on Methods for Manufacturing Spherical Silica>
[0272] To observe the porous structure of the cross-section of the spherical silica particles in each spherical silica powder, the shapes of Preparation Examples 1, 2 and Comparative Example 2 were compared and analyzed using a scanning electron microscope (FE-SEM).
[0273] In addition, the shapes of Preparation Example 1 and Comparative Example 1 were compared and analyzed using transmission electron microscopy (TEM).
[0274] On the other hand, in order to observe the cross-sectional structure of the spherical silica particles, each sample was processed and cut using a focused ion beam, and its cross-sectional structure was photographed.
[0275] The images taken are as follows Figures 3 to 7 As shown.
[0276] Figure 3 This is a scanning electron microscope (FE-SEM) image of the cross-section of the spherical silica particles prepared according to Example 1 of the present invention.
[0277] Figure 4 This is a scanning electron microscope (FE-SEM) image of the cross-section of the spherical silica particles prepared according to Example 2 of the present invention.
[0278] Figure 5 This is a scanning electron microscope (FE-SEM) image of the cross-section of a spherical silica particle according to Comparative Example 2 of the present invention.
[0279] Figure 6 This is a transmission electron microscope (TEM) image of the cross-section of the spherical silica particles prepared according to Example 1 of the present invention.
[0280] Figure 7 This is a transmission electron microscope (TEM) image of the cross-section of a spherical silica particle according to Comparative Example 1 of the present invention.
[0281] Reference Figure 3 , Figure 4 and Figure 6 Both the spherical silica particles with narrow shell regions according to Preparation Example 1 and the spherical silica particles with wide shell regions according to Preparation Example 2 exhibited a trend where the pore size increases to 50 nm closer to the center of the core region and decreases to 5 nm closer to the outermost edge of the shell region. This confirms that the first pore size within the core region is 100 nm or less, and the second pore size within the shell region is 20 nm or less.
[0282] In particular, it can be seen that the pore size gradually decreases from the core to the shell.
[0283] On the other hand, refer to Figure 6 According to the cross-section of the spherical silica particles prepared in Example 1 as described above, the central pore diameter increases closer to the core region and decreases closer to the outermost periphery of the shell. This confirms that, unlike the core, the shell has a relatively dense structure.
[0284] Conversely, refer to Figure 7 According to Comparative Example 1, the cross-section of the silica particles has a dense distribution of pores of about 100 nm from the center of the particle to the outermost edge of the particle. This confirms that it does not have a core-shell structure with a gradient porous structure like the spherical silica particles prepared according to Example 1 or Example 2.
[0285] In addition, refer to Figure 5 Based on the fact that the cross-section of the silica particles in Comparative Example 2 has almost no pores or only small pores, it can be confirmed that, like Comparative Example 1, they do not have a gradient porous structure or a core-shell structure.
[0286] <Experimental Example 2 - Comparison of Particle Size Distribution and Oil Absorption Based on Spherical Silica Manufacturing Method>
[0287] To compare the physical properties of preparation examples 1 and 2 and comparative examples 1 to 3, particle size distribution analysis (PSA) and oil absorption analysis (OA) were performed.
[0288] Table 1 shows the particle size distribution analysis (PSA) and oil absorption analysis (OA) measurements of the spherical silica prepared in Examples 1, 2 and Comparative Examples 1 to 3.
[0289] Table 1
[0290]
[0291] Referring to Table 1, it can be confirmed that the average particle size of Preparation Examples 1 and 2 and Comparative Examples 1 to 3 are all in the range of 4 to 6 μm.
[0292] On the other hand, it can be confirmed that the spherical silica prepared in Examples 1 and 2 has a lower oil absorption than that of Comparative Example 1, which is manufactured by a conventional wet process. This confirms that the overall pore size is denser compared to the wet manufacturing method. Furthermore, it is confirmed that the oil absorption of Examples 1 and 2 differs from that of Comparative Example 2, which is manufactured by a conventional dry process, by less than ±0.25. Based on these findings, it is believed that the spherical silica prepared in Examples 1 and 2 provides similar oil absorption characteristics to Comparative Example 2, which is manufactured by a conventional dry process, while offering the advantage of low manufacturing cost due to the use of only a wet manufacturing method.
[0293] On the other hand, it was confirmed that the spherical silica prepared in Examples 1 and 2 had an oil absorption difference of less than ±0.08 compared with conventional PMMA organic microbeads, which indicates that when applied to cosmetic compositions, it provides oil absorption properties similar to PMMA.
[0294] <Experimental Example 3 - Comparison of Pore Distribution and Surface Properties Based on Spherical Silica Manufacturing Methods>
[0295] To compare the pore distribution of the spherical silica particles prepared according to Examples 1 and 2 and Comparative Examples 1 and 2, specific surface area analysis (BET) was performed. The results are shown in Table 2 below.
[0296] Furthermore, the surface of the spherical silica particles prepared according to Example 1 was imaged using a scanning electron microscope (FE-SEM), and the results are as follows: Figure 8 As shown.
[0297] Table 2
[0298]
[0299] Referring to Table 2, it can be confirmed that the specific surface area of the spherical silica powder prepared according to Examples 1 and 2 is significantly smaller than that of the silica powder prepared by the wet process in Comparative Example 1.
[0300] Figure 8 This is a scanning electron microscope (FE-SEM) image of the surface of the spherical silica particles prepared according to Example 1 of the present invention.
[0301] For reference Figure 8 It can be confirmed that the surface pores of the shell in the spherical silica particles prepared in Example 1 are very small. This is consistent with the result that the spherical silica prepared in Example 1 has a lower specific surface area than that of Comparative Example 1 prepared by the wet process.
[0302] On the other hand, as can be confirmed in Table 1, the spherical silica particles prepared in Examples 1 and 2 exhibit a smaller oil absorption capacity compared to the silica particles prepared in Comparative Example 1, which is consistent with the specific surface area evaluation results in Table 2.
[0303] On the other hand, it can be confirmed that the specific surface area of the spherical silica powders prepared in Examples 1 and 2 is at the same level as that of the silica powder of Comparative Example 2 and the PMMA powder of Comparative Example 3 prepared using the dry process. From this, it can be concluded that the spherical silica powders prepared in Examples 1 and 2 are sufficient to replace silica powders and PMMA powders prepared using the conventional wet and dry processes.
[0304] <Experimental Example 4 - Comparison of Adsorption-Desorption Characteristics of Spherical Silica>
[0305] To compare and evaluate the changes in adsorption-desorption characteristics of the spherical silica particles according to embodiments of the present invention, adsorption-desorption isotherms were measured.
[0306] In addition, adsorption-desorption isotherms were measured to compare the changes in adsorption-desorption characteristics of silica particles according to the comparative example.
[0307] The adsorption-desorption characteristics were evaluated using nitrogen gas for the powders prepared in Examples 1 and 2, and Comparative Examples 1 to 3. The results are as follows: Figures 9a to 9e As shown.
[0308] Figure 9a and 9b The nitrogen adsorption-desorption isotherms of the spherical silica particles prepared according to Examples 1 and 2 of the present invention are shown.
[0309] Figures 9c to 9e The nitrogen adsorption-desorption isotherms of silica particles according to Comparative Examples 1 to 3 of the present invention are shown.
[0310] Reference Figure 9a and Figure 9b It can be confirmed that in the nitrogen adsorption-desorption isotherms of preparation examples 1 and 2, a wide and long hysteresis loop is observed above a relative pressure of 0.45.
[0311] Reference Figures 9c to 9e It can be confirmed that the organic microspheres of silica according to Comparative Examples 1 and 2 and PMMA according to Comparative Example 3 have fewer hysteresis loops in the nitrogen adsorption-desorption isotherms at relative pressures above 0.9.
[0312] These findings confirm that the spherical silica particles prepared according to Examples 1 and 2 exhibit a large hysteresis loop on the nitrogen adsorption-desorption isotherm within a specific relative pressure range. This characteristic can be explained by the ink bottle effect on the nitrogen isotherm caused by the continuous and gradual change in pore structure from the macropore distribution of the core to the micropore connection of the shell. Therefore, it can be concluded that the spherical silica powder prepared according to Examples 1 and 2 can fully replace silica powder and PMMA powder prepared using conventional wet and dry methods.
[0313] <Preparation Example - Manufacturing of a Cosmetic Composition Containing Spherical Silica Particles>
[0314] The spherical silica of the present invention has the advantages of excellent feel and adhesion. To confirm this, a cosmetic composition comprising the spherical silica of the present invention was manufactured.
[0315] Using silica particles and organic microbeads (PMMA) prepared according to Examples 1, 2 and Comparative Examples 1 to 3 of the present invention, a powder foundation cosmetic composition was manufactured according to the composition shown in Table 3 below.
[0316] Table 3
[0317]
[0318] <Experimental Example 5 - Sensory Evaluation of Cosmetic Compositions>
[0319] To compare and evaluate the usability and adhesion of the cosmetic compositions prepared according to Examples 2.1, 2.2 and Comparative Examples 2.1 to 2.3, sensory evaluations were performed as follows.
[0320] First, 10 women and 10 men aged 20 to 40 were selected as sensory evaluation subjects. Subjects applied Preparation Examples 2.1, 2.2, and Comparative Examples 2.1 to 2.3 directly to their skin and gave sensory evaluations on a scale of 1 to 5 based on the feel of adhesion and usability. The average of these scores was then calculated to arrive at the final sensory evaluation score.
[0321] Among them, adhesion refers to the degree to which the foundation adheres to the skin, that is, the adhesion, which means the degree to which the product is seamlessly applied to the skin surface and stays in place for a long time.
[0322] The aforementioned user experience refers to the immediate sensation felt when applying the cosmetic composition to the face. This includes the softness, spreadability, and tactile sensation felt when spreading a small amount of the formulation and applying it to the skin.
[0323] The results are shown in Table 4 below.
[0324] Table 4
[0325]
[0326] Referring to Table 4, it can be confirmed that the overall scores of Preparation Examples 2.1 and 2.2 are higher than those of Comparative Examples 2.1 and 2.2. In particular, it can be confirmed that the cosmetic compositions according to Preparation Examples 2.1 and 2.2 provide a better user experience than the cosmetic composition according to Comparative Example 2.2, which contains silica particles produced by dry processing. Furthermore, since the cosmetic compositions according to the Preparation Examples have a higher overall score than the cosmetic composition according to Comparative Example 2.3, which contains PMMA organic microbeads, it can be concluded that the spherical silica particles according to Preparation Examples 1 and 2 are sufficient to replace the PMMA organic microbeads according to Comparative Example 3.
[0327] <Preparation Example - Manufacturing of Silica Dispersion>
[0328] Next, in order to manufacture a silica dispersion according to an embodiment of the present invention, a silica dispersion was manufactured using the spherical silica of the present invention described above.
[0329] Specifically, the spherical silica powders prepared according to Examples 1 and 2 and Comparative Examples 1 and 2 of the present invention were mixed in a dispersion medium at a concentration of 20 wt% as solids.
[0330] At this point, the dispersion medium used is diisostearyl malate (DIS), which is an ester oil.
[0331] That is, after dispersing the spherical silica powders prepared according to Examples 1 and 2 and Comparative Examples 1 and 2 in DIS at a concentration of 20 wt% under the same conditions, high shear agitation was performed on the mixture to produce a silica dispersion in which spherical silica is uniformly dispersed in the dispersion medium.
[0332] At this point, before performing a Turbiscan measurement, the silica dispersion is stirred at a speed of 3000 rpm or higher for at least 1 minute to fully disperse until no residual powder is visible to the naked eye at the bottom of the dispersion manufacturing container.
[0333] Finally, the air bubbles in the homogenized silica dispersion were removed.
[0334] On the other hand, the manufacturing methods and conditions described above are summarized in Table 5 below.
[0335] Table 5
[0336]
[0337] <Experimental Example 6 - Comparison of Dispersion Stability of Spherical Silica Dispersions Based on Spherical Silica Manufacturing Methods>
[0338] First, in order to confirm the difference in dispersion stability caused by the difference in the internal pore structure of spherical silica in the silica dispersion, the tap density of spherical silica prepared according to Examples 1 and 2 and Comparative Examples 1 and 2 was measured.
[0339] After drying each sample, fill a measuring container of a specified capacity with a certain mass and repeatedly tap it according to the conditions standardized by ASTM B527, ISO787 or JIS K 5101.
[0340] Then, the volume of the powder layer after stabilization was recorded, and the tap density of each sample was calculated by dividing the powder mass by the stabilized volume using the following formula.
[0341]
[0342] Where, ρ t M is the tap density, V is the powder mass, and M is the tap density. t The volume of the powder layer stabilized after tapping. Furthermore, the powder layer refers to the state in which powder particles collectively occupy the total volume before or after tapping when a certain mass of powder is added to a container during tap density measurement.
[0343] On the other hand, in order to make the difference in tap density mainly reflect the influence caused by the difference in internal pore structure and true sphericity, the average particle size (D50) of Preparation Examples 1 and 2 and Comparative Examples 1 and 2 was adjusted to not produce large differences.
[0344] The tap density measurement results for each sample are shown in Table 6 below.
[0345] Table 6
[0346]
[0347] Referring to Table 6, the tap density of the spherical silica prepared according to Preparation Example 1 and the spherical silica prepared according to Preparation Example 2 is in the range of 0.40 g / mL to 0.95 g / mL.
[0348] On the other hand, this can be explained by the difference in the proportion of the core region and the shell region, as well as the porosity distribution, between Preparation Example 1 and Preparation Example 2 (for example, the shell region proportion in Preparation Example 1 is relatively smaller than that in Preparation Example 2; see [link to relevant documentation]). Figure 3 and Figure 4 Therefore, differences appeared in the tap density.
[0349] Next, to compare the dispersion stability of the silica dispersions prepared according to the above method in Examples 3.1, 3.2 and Comparative Examples 3.1, 3.2, the Turbiscan Stability Index (TSI) was measured. The results are as follows: Figures 10 to 13 As shown.
[0350] Figure 10 This is a graph showing the change in Turbiscan stability index (TSI) of the silica dispersion prepared using the spherical silica of Example 1 of the present invention.
[0351] Figure 11 This is a graph showing the change in Turbiscan stability index (TSI) of the silica dispersion prepared using the spherical silica of Example 2 of the present invention.
[0352] Figure 12 This is a graph showing the change in Turbiscan stability index (TSI) of the silica dispersion using spherical silica of Comparative Example 1 of the present invention.
[0353] Figure 13 This is a graph showing the change in Turbiscan stability index (TSI) of the silica dispersion using spherical silica of Comparative Example 2 of the present invention.
[0354] On the other hand, the BS / T spectrum used in the above TSI measurement was obtained based on the measurement conditions described later, and the results are as follows: Figures 14 to 17 As shown.
[0355] Figure 14 This is a graph showing the changes in the transmittance and backscattering intensity of the silica dispersion prepared using the spherical silica of Example 1 of the present invention.
[0356] Figure 15 The graph shows the changes in transmittance and backscattering intensity of the silica dispersion prepared using the spherical silica of Example 2 of the present invention.
[0357] Figure 16 This is a graph showing the changes in transmittance and backscattering intensity of the silica dispersion using the spherical silica of Comparative Example 1 of the present invention.
[0358] Figure 17 This is a graph showing the changes in transmittance and backscattering intensity of the silica dispersion using the spherical silica of Comparative Example 2 of the present invention.
[0359] The Figures 10 to 17 The chart shows the results of measurements taken at 25°C for 3 hours.
[0360] The TSI of each silica dispersion was calculated by applying the aforementioned mathematical formula 1 to the BS / T spectrum obtained in this way, and the results are shown in Table 7 below.
[0361] Table 7
[0362]
[0363] Referring to Table 7, the TSI of Preparation Examples 3.1 and 3.2, which respectively include Preparation Examples 1 and 2 with gradient porous structures, is lower than that of Comparative Example 3.2, and is in the range of 0.30 or below.
[0364] Especially referencing Figure 14 and Figure 15 In the BS / T spectra of the silica dispersions in Preparation Examples 3.1 and 3.2, which contain spherical silica with a gradient porous structure, the changes (deviations) in transmittance and backscattering intensity between multiple measurements were smaller than those in Comparative Examples 3.1 and 3.2 for regions other than the meniscus.
[0365] This may suggest that the silica dispersions in Preparation Examples 3.1 and 3.2 underwent restricted coagulation or precipitation over time, which can be explained by the absence of stratified bands in the T and BS spectra.
[0366] Conversely, refer to Figure 16 and Figure 17 Comparative Example 3.1, containing spherical silica with a random porous structure, and Comparative Example 3.2, containing spherical silica with a dense structure, both showed intensity deviations between multiple measurements in the BS / T spectra for regions other than the meniscus.
[0367] This can be explained by the fact that, as the silica dispersions of Comparative Examples 3.1 and 3.2 both agglomerated or precipitated over time, layered bands appeared in the spectra measured multiple times.
[0368] On the other hand, the tap density of the spherical silica according to Comparative Example 2 is in the range of 0.40 g / mL to 0.95 g / mL.
[0369] Furthermore, in the case of the silica dispersion according to Comparative Example 3.2, although the TSI value was low, it showed that the dispersion stability, including the spatial concentration distribution, needed to be judged together with the BS / T spectrum.
[0370] Specifically, in the silica dispersion according to Comparative Example 3.2, as referred to Figure 17 As can be seen from the BS / T spectrum, intensity differences were observed along the sample height, suggesting the possible existence of spatial concentration gradients or local non-uniformity within the sample. Therefore, this can be interpreted as potentially disadvantageous in terms of long-term stability compared to the application of spherical silica with a gradient porous structure, as in Examples 3.1 and 3.2 of this invention.
[0371] Conversely, the silica dispersions prepared in Examples 3.1 and 3.2 maintained low TSI levels while meeting the tap density requirements for spherical silica, and showed almost no intensity deviation over time in the BS / T spectra.
[0372] Therefore, even when spherical silica powder with a gradient porous structure is contained in a dispersion medium at a high concentration of about 20 wt%, the aggregation or precipitation between particles in the dispersion system is limited over time, thus it can be evaluated as a silica dispersion with excellent dispersion stability.
[0373] The foregoing description of the present invention is for illustrative purposes. Those skilled in the art will understand that other specific forms can be readily derived without altering the technical concept or essential features of the invention. Therefore, it should be understood that the embodiments described above are exemplary and not restrictive in all respects. For example, the constituent elements described as a single type can be implemented separately, and similarly, the constituent elements described separately can be implemented in a combined form.
[0374] The scope of this invention is shown by the appended claims rather than the detailed description above, and the meaning and scope of the claims and all changes or modifications derived from their equivalents should be interpreted as being included within the scope of this invention.
Claims
1. A spherical silica, comprising a plurality of spherical silica particles, each of the plurality of said spherical silica particles comprising: A core containing multiple first pores and composed of silicon dioxide; A shell composed of the same silicon dioxide as the core and containing a second pore that is different from the first pore.
2. The spherical silica according to claim 1, wherein: The core and the shell are continuously connected along the central direction in the spherical silica particles to form a main body.
3. The spherical silica according to claim 1, wherein: The first pore has a size of less than 100 nm. The second pore has a size of less than 20 nm.
4. The spherical silica according to claim 1, wherein: From the shell to the core, the size of the second pore gradually increases, and at the position where the shell and the core meet, the size of the second pore is the same as the size of the first pore.
5. The spherical silica according to claim 1, wherein: The spherical silica particles have a tap density of 0.40 g / mL to 0.95 g / mL, as measured by any of the methods in ASTM B527, ISO 787, and JIS K 5101.
6. The spherical silica according to claim 1, wherein: The average particle size D50, as determined by particle size analysis, ranges from 0.5 to 30 μm.
7. The spherical silica according to claim 6, wherein: The thickness of the core is less than 99% of the total diameter of the cross-section of the spherical silica particles.
8. The spherical silica according to claim 6, wherein: The thickness of the shell is less than 50% of the total diameter of the cross-section of the spherical silica particles.
9. The spherical silica according to claim 1, wherein: The oil absorption of the powder, as determined by oil absorption analysis, ranges from 0.2 to 120 mL / g.
10. The spherical silica according to claim 1, wherein: The specific surface area measured based on specific surface area analysis is 100 m². 2 / g or less.
11. The spherical silica according to claim 1, wherein: The spherical silica is configured to allow for the adsorption and desorption of substances through multiple first and second pores. The relative pressure required to adsorb the spherical silica particles is different from the relative pressure required to desorb them.
12. A silica dispersion, comprising: Dispersion medium; Spherical silica dispersed in the dispersion medium The spherical silicon dioxide comprises: A core comprising multiple first pores and composed of silicon dioxide; and A shell composed of the same silicon dioxide as the core and containing a second pore that is different from the first pore.
13. The silica dispersion according to claim 12, wherein: Based on the solid content, the spherical silica is contained in the dispersion medium at a concentration of 10 wt% to 20 wt%.
14. The silica dispersion according to claim 12, wherein: The Turbiscan stability index of the silica dispersion, measured using a Turbiscan instrument at 25°C, was below 0.
30.
15. The silica dispersion according to claim 12, wherein: The dispersion medium includes at least one of hydrocarbon oils, ester oils, vegetable oils, and silicone oils.
Citation Information
Patent Citations
Hollow silica particles, compositions comprising them, and methods for making same
KR1020080028992A
